Penguatan Pendidikan Karakter Peserta Didik Melalui Budaya Sekolah di SMP Negeri 3 Jawai Selatan Kabupaten Sambas - Aldi; Wiyono, Hadi; Atmaja , Thomy Sastra (PTK: Jurnal Tindakan Kelas, 2025)
One important aspect to form a generation with morals and integrity in the midst of increasingly complex developments is character education. The purpose of this study was to analyze the strengthening of character education with school culture at SMP Negeri 3 Jawai Selatan which consists of routine activities, spontaneous, exemplary, and conditioning. This study uses a qualitative descriptive method. Data were taken through observation, interviews with informants, namely the principal, social studies teachers, and 6 students, and through documentation. Data analysis used data reduction techniques, and data presentation, as well as drawing conclusions and verification. The result is the strengthening of character education at SMP Negeri 3 Jawai Selatan with routine activities, spontaneous, exemplary, and conditioning. Routine activities consist of flag ceremonies, congregational Dzuhur prayers, singing national songs during ceremonies, reading the Qur'an, and hair raids. Spontaneous activities include giving sanctions to students who fight, litter, are not neat in their clothes, are caught cheating, are caught stealing, and say bad words. Exemplary activities are the exemplary behavior of teachers, principals, students, school staff, and school residents in attitudes and behaviors such as dressing, speaking, acting, personal hygiene, and discipline. Conditioning activities are creating a clean school environment, clean toilets, clean classrooms, clean teachers' rooms, clean gardens, posting motivational/wise words containing character, and extracurricular activities.